S = 4 ( 1 ) 4 + 1 1 + 4 ( 2 ) 4 + 1 2 + 4 ( 3 ) 4 + 1 3 + ⋯ + 4 ( 2 0 1 6 ) 4 + 1 2 0 1 6
If the sum above S = 2 0 1 7 q + 1 2 0 1 7 p , where p and q are positive integers , find p + q .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for your solution!
Log in to reply
Your hint completely gave it away...
Log in to reply
Oh, I should remove the hint to higher the difficulty of this problem.
even i used the sophie germain identity
4 x 4 + 1 x ≡ 2 x 2 − 2 x + 1 A + 2 x 2 + 2 x + 1 B ≡ 2 x ( x − 1 ) + 1 A + 2 x ( x + 1 ) + 1 B
x ≡ A ( 2 x 2 + 2 x + 1 ) + B ( 2 x 2 − 2 x + 1 )
⇒ A = 4 1 , B = − 4 1
4 ( 1 ) 4 + 1 1 + 4 ( 2 ) 4 + 1 2 + 4 ( 3 ) 4 + 1 3 + ⋯ + 4 ( 2 0 1 6 ) 4 + 1 2 0 1 6
= 4 1 ( ( 2 ( 1 ) ( 1 − 1 ) + 1 1 − 2 ( 1 ) ( 1 + 1 ) + 1 1 ) + ( 2 ( 2 ) ( 2 − 1 ) + 1 1 − 2 ( 2 ) ( 2 + 1 ) + 1 1 ) + ( 2 ( 3 ) ( 3 − 1 ) + 1 1 − 2 ( 3 ) ( 3 + 1 ) + 1 1 ) + ⋯ + ( 2 ( 2 0 1 6 ) ( 2 0 1 6 − 1 ) + 1 1 − 2 ( 2 0 1 6 ) ( 2 0 1 6 + 1 ) + 1 1 ) )
= 4 1 ( ( 1 1 − 5 1 ) + ( 5 1 − 1 3 1 ) + ( 1 3 1 − 2 5 1 ) + ⋯ + 2 ( 2 0 1 6 ) ( 2 0 1 6 − 1 ) + 1 1 − 2 ( 2 0 1 6 ) ( 2 0 1 6 + 1 ) + 1 1 ) )
= 4 1 ( 1 − 4 0 3 2 ( 2 0 1 7 ) + 1 1 )
= 4 1 ( 4 0 3 2 ( 2 0 1 7 ) + 1 4 0 3 2 ( 2 0 1 7 ) + 1 − 1 )
= 4 0 3 2 ( 2 0 1 7 ) + 1 1 0 0 8 ( 2 0 1 7 )
⇒ p + q = 1 0 0 8 + 4 0 3 2 = 5 0 4 0
Problem Loading...
Note Loading...
Set Loading...
S = n = 1 ∑ 2 0 1 6 4 n 4 + 1 n = n = 1 ∑ 2 0 1 6 ( 2 n 2 − 2 n + 1 ) ( 2 n 2 + 2 n + 1 ) n = 4 1 n = 1 ∑ 2 0 1 6 ( 2 n 2 − 2 n + 1 1 − 2 n 2 + 2 n + 1 1 ) = 4 1 ( n = 1 ∑ 2 0 1 6 2 n 2 − 2 n + 1 1 − n = 1 ∑ 2 0 1 6 2 n 2 + 2 n + 1 1 ) Let n = m − 1 = 4 1 ( n = 1 ∑ 2 0 1 6 2 n 2 − 2 n + 1 1 − m = 2 ∑ 2 0 1 7 2 ( m − 1 ) 2 + 2 ( m − 1 ) + 1 1 ) = 4 1 ( n = 1 ∑ 2 0 1 6 2 n 2 − 2 n + 1 1 − m = 2 ∑ 2 0 1 7 2 m 2 − 2 m + 1 1 ) Putting m = n = 4 1 ( n = 1 ∑ 2 0 1 6 2 n 2 − 2 n + 1 1 − n = 2 ∑ 2 0 1 7 2 n 2 − 2 n + 1 1 ) = 4 1 ( 1 − 2 ( 2 0 1 7 ) 2 − 2 ( 2 0 1 7 ) + 1 1 ) = 4 1 ( 1 − 2 0 1 7 ⋅ 4 0 3 2 + 1 1 ) = 4 1 ( 2 0 1 7 ⋅ 4 0 3 2 + 1 2 0 1 7 ⋅ 4 0 3 2 ) = 2 0 1 7 ⋅ 4 0 3 2 + 1 2 0 1 7 ⋅ 1 0 0 8
⟹ p + q = 1 0 0 8 + 4 0 3 2 = 5 0 4 0